Structural basis of prolyl hydroxylase domain inhibition by Molidustat - Figg, WD; McDonough, MA; Chowdhury, R; Nakashima, Y; Zhang, Z; Holt-Martyn, JP; Krajnc, A; Schofield, CJ (Wiley, 2021)
Human prolyl-hydroxylases (PHDs) are hypoxia-sensing 2-oxoglutarate (2OG) oxygenases, catalysis by which suppresses the transcription of hypoxia-inducible factor target genes. PHD inhibition enables the treatment of anaemia/ischaemia-related disease. The PHD inhibitor Molidustat is approved for the treatment of renal anaemia; it differs from other approved/late-stage PHD inhibitors in lacking a glycinamide side chain. The first reported crystal structures of Molidustat and IOX4 (a brain-penetrating derivative) complexed with PHD2 reveal how their contiguous triazole, pyrazolone and pyrimidine/pyridine rings bind at the active site. The inhibitors bind to the active-site metal in a bidentate manner through their pyrazolone and pyrimidine nitrogens, with the triazole π-π-stacking with Tyr303 in the 2OG binding pocket. Comparison of the new structures with other PHD inhibitor complexes reveals differences in the conformations of Tyr303, Tyr310, and a mobile loop linking β2-β3, which are involved in dynamic substrate binding/product release.